Non-Labor Income and the Age of Marriage: Evidence from China's Heating Policy - Junhong Chu; Haoming Liu; I. P. L. Png (Institute of Labor Economics (IZA), 2018)
We exploit China's heating policy to investigate how non-labor income affects marriage. From the mid-1950s, the policy gave substantial subsidies to urban residents north of the Huai River. Applying geographic regression discontinuity, we find that, with the policy, urban men in the north married 15 months earlier than southerners. The difference is substantial compared with the average age of first marriage of 24.9 years for urban men in the south. The effect is larger for later birth cohorts, which is consistent with the progressive implementation of the policy. The effect is smaller among women, consistent with women having less power in the household than men. There is no effect among rural people, who did not benefit from the heating policy.
Keywords: J12; 330; age at marriage; regression discontinuity; non-labor income; China